PERSEPSI GURU PAMONG TERHADAP PELAKSANAAN PLK MAHASISWA PENDIDIKAN SENDRATASIK DI SMK NEGERI KOTA PADANG SEMESTER JANUARI-JUNI 2019 - Yudesyone, Jesica; Darmawati, Darmawati (SENDRATASIK UNP, 2019)
Abstract  This article aims to determine the perception of teachers toward the PLK implementation of Sendratasik College Students at SMK Negeri Kota Padang in Semester January-June 2019. Type of the research was qualitative descriptive research. The main instrument of this research was the resarcher and it was supported by supporting instruments such as stationery, camera and mobile phone. The type of data used were primary and secondary data. Techniques of data collection were done by using library study, observation, interview and documentation. The steps in analyzing data were conducted by doing data collection, analyzing data, describing data and making conclusion. The results shows that the college students’ teaching skill in ballet are still lacked deficiencies and have to be corrected during the micro teaching lecture. It is because most of students do not prepare the media for learning, from the beginning until the end of PLK, the college students do not make media device at all. The ability in communicating, actually the college students can open-minded in receiving criticism and advice from students, teachers, employees in the school and showing a friendly attitude in and out of school. Keywords: Teachers Perception, The PLK Implementation of Sendratasik College Students